Guilherme De Almeida Em Revistas: A Poesia Publicada Nos Periódicos Modernistas - Santos, Andre Felipe Barbosa Da Silva [UNIFESP] (2017)
The debate concerning the role of the literary journals as an essential part of the modernism movement in Brazil has received more attention from the contemporary literary criticism. Based on that, the study of the literature produced and released through the magazines allows us to realize how the artists comprehended the values of the modernity in the beginning of the twentieth century as well as they put them into broader circulation. Therefore, the aim of this M. A. thesis consists of collecting and analyzing fourteen poems written by Guilherme de Almeida (1890-1969) and originally published in eight literary journals from the southeast region, between 1922 and 1929: Klaxon (1922-23), Árvore Nova (1923), Estética (1924-25), A Revista (1926), Terra roxa e outras terras (1926), Verde (1927), Revista de Antropofagia (1928) and Movimento Brasileiro (1929). The analyses point to compositions that would promote the rhythm as a poetic manifestation. Thus, this research emphasizes new possibilities of reading and interpretation manifested throughout the relationship established between the texts in the magazines.